Edukasi Makanan Sehat Balita Sebagai Pencegahan Stunting di Desa Wonosari, Kabupaten Penajam Paser Utara, Kalimantan Timur - Siddiq, Muhammad Nuzul Azhim Ash; Hajrah, Hajrah; Gama, Noviyanty Indjar; Hikmawan, Baso Didik; Wijaya, Viriyanata; Zamruddin, Nur Masyithah; Hamdani, Hamdani; Pangesti, Rizka Dhilla Dwi; Irawan, Adithya Rizky (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2023)
Providing healthy food education for toddlers is one of the efforts in overcoming the problem of stunting. Providing education, counseling, and behavior change is included in the form of sensitive nutrition interventions, namely increasing awareness of parenting and nutrition for toddlers. The community service activity aims to increase the nutritional knowledge of mothers of toddlers on healthy and nutritious foods for toddlers and determine the relationship with the incidence of stunting. The methods used in this activity are lecturers delivering educational content directly to mothers of toddlers with the aid of visual media in the form of PowerPoint presentations. Pre and post-test questionnaires were given before and after education to measure the nutritional knowledge of mothers of toddlers. The nutritional knowledge scores obtained were statistically analyzed using Paired T-Test. The results of statistical analysis showed that there was a significant increase (p<0.05) in the mothers' knowledge scores before and after education. The service team also provided several examples of healthy foods for toddlers, especially complementary foods that are easy to make as an alternative to feeding children under five.